Efektivitas Program Pelayanan Identitas Kependudukan Digital Di Kelurahan Kandangan Kota Surabaya - Moch Andre Firmansyah; Rosyidatuzzahro Anisykurlillah (Jurnal Ilmiah Wahana Pendidikan, 2023)
In the era of digitalization, the development of technology and information is growing. One of the developments in the digitalization era is in government services. One of these developments is the Digital Population Identity service program. The purpose of this Digital Resident Identity is to facilitate and accelerate public service transactions in digital form. The purpose of this study is to analyze the effectiveness of the Digital Population Identity service program in the Kandangan Village. This research method uses a qualitative approach using descriptive methods. Data collection was carried out through interviews, observation, and documentation. This study refers to the theory of effectiveness which consists of 4 (four) indicators, namely the accuracy of program targets, program socialization, achievement of program goals, and program monitoring. The results of the study show that the effectiveness of the Digital Resident Identity service program in the Kandangan Village, Surabaya City: 1) there is an increase in the enthusiasm of residents in activating Digital Citizenship Identity. 2) Kelurahan Kandangan, Heads of RT and RW, and the Surabaya City Population and Civil Registry Team also participated in disseminating information about IKD services in Kandang Village. 3) residents of the Kandangan Village are gradually switching from physical KTPs to digital KTPs, the aim of which is to facilitate and accelerate public service transactions in digital form. 4) the Kandangan Urban Village team and the Surabaya City Population and Civil Registry Office have monitored the Digital Population Identity service program in the Kandangan Village.